Dermacentor reticulatus: a vector on the rise - Földvári, Gábor; Široký, Pavel; Szekeres, Sándor; Majoros, Gábor; Sprong, Hein (Parasites & vectors, 2016)
Dermacentor reticulatus is a hard tick species with extraordinary biological features. It has a high reproduction rate, a rapid developmental cycle, and is also able to overcome years of unfavourable conditions. Dermacentor reticulatus can survive under water for several months and is cold-hardy even compared to other tick species. It has a wide host range: over 60 different wild and domesticated hosts are known for the three active developmental stages. Its high adaptiveness gives an edge to this tick species as shown by new data on the emergence and establishment of D. reticulatus populations throughout Europe. The tick has been the research focus of a growing number of scientists, physicians and veterinarians. Within the Web of Science database, more than a fifth of the over 700 items published on this species between 1897 and 2015 appeared in the last three years (2013-2015). Here we attempt to synthesize current knowledge on the systematics, ecology, geographical distribution and recent spread of the species and to highlight the great spectrum of possible veterinary and public health threats it poses. Canine babesiosis caused by Babesia canis is a severe leading canine vector-borne disease in many endemic areas. Although less frequently than Ixodes ricinus, D. reticulatus adults bite humans and transmit several Rickettsia spp., Omsk haemorrhagic fever virus or Tick-borne encephalitis virus. We have not solely collected and reviewed the latest and fundamental scientific papers available in primary databases but also widened our scope to books, theses, conference papers and specialists colleagues' experience where needed. Besides the dominant literature available in English, we also tried to access scientific literature in German, Russian and eastern European languages as well. We hope to inspire future research projects that are necessary to understand the basic life-cycle and ecology of this vector in order to understand and prevent disease threats. We conclude that although great strides have been made in our knowledge of the eco-epidemiology of this species, several gaps still need to be filled with basic research, targeting possible reservoir and vector roles and the key factors resulting in the observed geographical spread of D. reticulatus.
Keywords: Host Specificity; Demography; omská hemoragická horečka; psi; stadia vývoje; Encephalitis Viruses, Tick-Borne; Babesia; Hemorrhagic Fever, Omsk; Humans; Dogs; Arachnid Vectors; viry klíšťové encefalitidy; Babesiosis; Spread; Public Health; Asie; veřejné zdravotnictví; lidé; Epidemiology; zvířata; Europe; Geographical distribution; Host associations; nemoci přenášené klíšťaty; arachnida jako vektory; Tick-Borne Diseases; Dermacentor reticulatus; hostitelská specificita; Omsk haemorrhagic fever virus; klasifikace; nemoci psů; babezióza; Classification; infestace klíšťaty; Asia; demografie; Dog Diseases; Life Cycle Stages; Babesia canis; Animals; ekologie; Tick Infestations; Dermacentor; Evropa; Ecology